Remembrance Day practices in schools: meaning-making in social memory during the First World War centenary. Issue 1 (2nd January 2021) - Haight, Annie; Wright, Susannah; Aldridge, David; Alexander, Patrick
ABSTRACT: Each November, commemoration of the First World War armistice (and subsequent military events and conflicts) is almost ubiquitous in UK schools and has been given increased importance during the centenary years of the First World War. Yet as seemingly isolated occasions outside the regular curriculum, school practices of remembrance, and the understandings and perceptions surrounding them, have been subject to surprisingly little scrutiny. The Remembrance in Schools project (2013–19) investigates armistice commemoration in primary and secondary schools in three counties in southern England. This paper considers the theorisation of public commemorative rituals and relates this to teachers' reports of school-based events. It analyses teachers' accounts and perceptions, from survey and interview data, of the ways in which the First World War and subsequent conflicts are remembered, presented and discussed through school commemoration events. We conclude that such events mirror the 'social technologies' of public remembrance rituals. However, behind almost ubiquitous practices (the two-minute silence) and symbols (the poppy), these accounts reveal nuanced variations in teachers' views of the knowledge and values children gain from armistice commemoration in schools. These variations are inflected by individual schools' histories, community contexts, and pupil demographics, as well as teachers' own histories, values and ideals.